Influence of Maltodextrin and Spray Drying Process Conditions on Sugarcane Juice Powder Quality (2015)
Abstract. Food powder liquid extracts obtained from fruits and vegetables can be manufactured using spray drying technologies while maintaining the quality attributes that are required by the industrial sector. The aim of this study was to evaluate the effect of maltodextrin and spray drying process conditions on sugarcane juice powder. A central composite design was used with a response surface analysis of four factors: (A) maltodextrin (10-20%), (B) inlet air temperature (130-150 °C), (C) outlet air temperature (75- 85 °C) and (D) atomization speed (22,000–26,000 rpm). Moisture, hygroscopicity, solubility, effective recovery and formation of deposits on the walls presented significant differences (P0.05) with respect to all factors, while, for water activity, no statistical differences were observed. The optimization of the factors found for the drying operating conditions were: (A) 20%, (B) 130 °C, (C) 75 °C and (D) 22,000 rpm, respectively.